The Effect of Electroacupuncture on Dynamic Balance during Stair Climbing for Elderly Patients with Knee Osteoarthritis. (13th August 2020) - Hou, Meijin; Wang, Xiangbin; Yu, Jiao; Fu, Shengxing; Yang, Fengjiao; Li, Zhenhui; Zhang, Yanxin; Tao, Jing
Abstract : Background . Poor balance is one of the risk factors for falls in patients with knee osteoarthritis (KOA), which is related to the symptoms. Electroacupuncture (EA) is one of the traditional Chinese conservative methods commonly used to improve the symptoms in patients with KOA. Objective . To assess whether EA increases the dynamic balance during stair negotiation among patients with KOA. Methods . A total of 40 KOA patients were assigned to two groups randomly (true electroacupuncture vs. mock electroacupuncture). Acupoints around the knee were selected in the true electroacupuncture (TEA) group with electrical stimulation (2 Hz). In the mock electroacupuncture (MEA) group, about 2 cm next to the above acupoints, the needles were inserted superficially without electrical stimulation. All the participants received 11 sessions of stimulation treatment in three weeks. The primary outcome was margin of stability (MOS). Secondary outcomes included hip kinematics and kinetics as well as pain. Results . There was no significant difference between the two groups for self-reported pain (p = 0.585 ). During ascent, there was no difference between groups in MOS value in both directions, which was the anterior-posterior (A/P) direction and medial-lateral (M/L) direction at initial contact and toe-off as well as the midstance in the gait cycle, and no difference for the hip kinematics and kinetics between the groups was detected (p > 0.05 ). For descent, at the toe-off event, the TEA group was more unstable as compared to the MEA group in the A/P direction (p = 0.029 ) but not in the M/L direction, and the hip showed a larger internal rotator moment (p = 0.049 ); at the midstance, the TEA group showed a lower abductor moment than the MEA group (p = 0.003 ). Conclusions . Based on the assessment results from the chosen patients with KOA, the TEA did not demonstrate a significant effect in improving the dynamic balance during stair negotiation in comparison with the MEA. This finding does not support EA as a conservative treatment to improve the dynamic balance in such patients.